PRAKTEK ILLEGAL FISHING DI PERAIRAN MALUKU SEBAGAI BENTUK KEJAHATAN EKONOMI - Yanti Amelia Lewerissa (SASI, 2010)
The potential of fisheries in the waters of Maluku is so large that it is often used by other affiliated companies both local and foreign fish for fishing illegally. Illegal fishing practices, and brought most of the catch to foreign countries without going through the formal examination procedure proved to be the impact of revenue losses for local or central government. The core issue in this study is whether the practice of illegal fishing in the waters of Maluku can categorize as economic crimes. Writing method used in this paper is a type of juridical normative deskritif analytical writing. The study concluded that the effect caused by the existence of this criminal act, then the state and the Government of the Republic of Indonesia suffered losses and has led to delays in national development. Therefore, it kriminologi, illegal fishing, the type of crime can be classified into economic crimes.